2017
DOI: 10.1016/j.bbabio.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and mitochondrial dynamics-The cancer connection

Abstract: Mitochondrial dysfunction is a hallmark of many diseases. The retrograde signaling initiated by dysfunctional mitochondria can bring about global changes in gene expression that alters cell morphology and function. Typically, this is attributed to disruption of important mitochondrial functions, such as ATP production, integration of metabolism, calcium homeostasis and regulation of apoptosis. Recent studies showed that in addition to these factors, mitochondrial dynamics might play an important role in stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
250
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(265 citation statements)
references
References 152 publications
10
250
0
5
Order By: Relevance
“…Furthermore, mitochondria are the energy powerhouses of cells and make the most use of the cell’s ATP. Cancer cells consumed a large amount of energy supplied as ATP, so any disruption in this supply is likely to cause apoptosis of cell [39]. Our in vitro data demonstrate that treatment of QBC939 cells with resveratrol inhibited autophagy progression and increased the oxidative stress and MtD (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, mitochondria are the energy powerhouses of cells and make the most use of the cell’s ATP. Cancer cells consumed a large amount of energy supplied as ATP, so any disruption in this supply is likely to cause apoptosis of cell [39]. Our in vitro data demonstrate that treatment of QBC939 cells with resveratrol inhibited autophagy progression and increased the oxidative stress and MtD (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The inner mitochondrial membrane is extensively folded, producing invaginations called cristae, which control oxidative phosphorylation (OXPHOS), electron and metabolite transport, and cell death and survival (3). Consequently, mitochondrial network dysregulation is linked to several pathophysiological conditions, including cancer, diabetes, and neurodegenerative diseases (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Conversely, mitochondrial dynamics is controlled by mitochondrion-shaping proteins that regulate fusion and fission events. Core components of the mitochondrial fusion/ fission machinery include mitofusin 1 (MFN1), mitofusin 2 (MFN2), and optic atrophy 1 (OPA1), which promote fusion, whereas fission is governed by dynamin-related protein 1 (DRP1) and by adaptor proteins such as mitochondrial fission factor (MFF), mitochondrial dynamics proteins (MiD49 and MiD51), and fission 1 (FIS1) (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Mitochondrial fission and fusion allow rapidly morphological changes in response to physiological and pathological conditions [45][46][47]. Dysfunction in mitochondrial dynamics is related to many neurodegenerative diseases, underpinning the role of fission and fusion in the maintenance of cellular homeostasis [46,48,49]. We observed that ALA-SDT could induce a decrease in mitochondrial membrane potential and ATP production, which means the initiation of mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 83%
“…Though cancer cells are relatively independent of mitochondrial oxidative pathways for ATP production, mitochondria still play a crucial role in regulating cellular homeostasis and cell death [43,44]. Mitochondrial fission and fusion allow rapidly morphological changes in response to physiological and pathological conditions [45][46][47]. Dysfunction in mitochondrial dynamics is related to many neurodegenerative diseases, underpinning the role of fission and fusion in the maintenance of cellular homeostasis [46,48,49].…”
Section: Discussionmentioning
confidence: 99%